First occurrences of Ni-V-Co phosphides in chromitite from the Agios Stefanos Mine, Othrys Ophiolite, Greece - Ifandi, Elena; Zaccarini, Federica; Tsikouras, Basilios; Grammatikopoulos, Tassos; Garuti, Giorgio; Karipi, Sofia; Hatzipanagiotou, Konstantin (Ofioliti, 2018)
Phosphide minerals, generally less than 20 μm in size, are mainly made of Ni-V-Co-Mo constituents, discovered in concentrates obtained from chromitite samples from the Agios Stefanos mine, Othrys ophiolite, Greece. Spinel from the chromitite is rich in Fe2O3and very similar to chromites from podiform chromitites. Its Cr/(Cr+Al) ratios are lower than those of chromites with a boninitic affinity. On the basis of their chemical compositions, the following phosphide minerals have been identified: melliniite, nickelphosphide and two phases that can be classified as (i) either Ni-allabogdanite or Ni-barringerite, and (ii) either V-allabogdanite or V-barringerite. Under reflected-light microscope, all the inspected phosphide minerals display similar reflectance and a creamy-yellowish color, despite their different compositions. Melliniite is isotropic, while nickelphosphide shows a weak anisotropism. The Ni-allabogdanite or Ni-barringerite and V-allabogdanite or V-barringerite display a strong anisotropism. They occur associated with awaruite, pentlandite, native vanadium, vanadium sulfides, Mo-Ni-V-Co alloy (probably hexamolybdenum), Hg selenide (possible tiemmanite) and several minerals composed of Ni, As and Sb. A few of them were in contact with chromite, chlorite, quartz and glass. This mineralogical assemblage suggests that the discovered minerals are natural in origin and they do not represent an artefact related to the sample preparation. Furthermore, it is suggested that the investigated minerals have been crystallized in a local reducing geochemical environment. During the serpentinization of peridotites, reducing fluids containing dissolved H2 are released from the reduction of H2O. Therefore, these phosphides and the associated minerals may have precipitated during the serpentinization process at low temperature. Nickel and cobalt may have been released during alteration of olivine or they were originally hosted in magmatic sulfides that were altered during the serpentinization. Phosphorous may represent an alteration product of apatite and olivine. Vanadium was probably released during the alteration of the host chromite. We speculate that Mo was originally hosted in sulfides or oxides and after its remobilization it was incorporated into the crystal lattice of the Mo-rich phases. Alternatively, the high reducing minerals of the Othrys may have formed because of the interaction of their host rock with a lightning. The stoichiometry of the analyzed phosphide minerals indicates that some grains found in the Othrys chromitites may represent new mineral species, such as Ni-allabogdanite or Ni-barringerite, as well as V-allabogdanite or V-barringerite. However, their small size and complex micro-intergrowths with other minerals inhibit the elaboration of an X-ray diffraction study, which would unequivocally determine their nature. To the best of our knowledge, melliniite and nickelphosphide in the Othrys chromitite represent the first finding of these rare minerals in terrestrial samples.